Characterizing Business Cycles in Small Economies - Hnatkovska, Viktoria; Koehler-Geib, Fritzi (World Bank, Washington, DC, 2018)
This paper aims to document a set of stylized facts characterizing business cycle dynamics in smaller economies. The paper uses a large sample of countries spanning 1960-2014 to show that country size is a significant factor affecting countries' volatility, comovement with gross domestic product and real interest rate, and persistence. Specifically, analysis finds that smaller countries (i) tend to have more volatile gross domestic product; (ii) have more volatile, less procyclical, and less persistent investment; (iii) exhibit more volatile trade balance and current account, have more procyclical exports, and thus less countercyclical trade balance; (iv) have more volatile government consumption and more procyclical public revenues and fiscal balance; and (v) possess more procyclical inflation. The effects of country size remain robust even after we control for the level of economic and institutional development, the presence of fiscal rule(s) and fixed exchange rates, and the commodity exporting status.